Study of yeast and sugar in bio-energy generation - Teng Howe Cheng; B. C. Kok; C. Uttraphan; M. H. Yee (Bulletin of Electrical Engineering and Informatics, 2020)
This paper demonstrates a simple and cost-effective bio-energy generation through biochemical reaction between yeast and sugar. Correlation of energy released between baker yeast Saccharomyces cerevisiae concentration and sugar solution concentration can be observed significantly over laboratory works. A certain number of electrons is released during the process of ethanol fermentation, in which sugars are broken down into ethanol and carbon dioxide. Consequently, bio-energy can be captured via two copper rods during the fermentation period from different concentration variables using the principle of microbial fuel cell (MFC). In this case, yeast and sugar have been selected as the concentration variables. The experiment works concluded that higher concentration of sugar solution correlates to the increment of energy output. However, the concentration of sugar beyond 0.6g/ml causes instability of the energy output. At the same time, another considerable limiting factor of the energy output is the area of separation membrane. The overabundance of sugar concentration can lead to adverse effects in harvesting the bio-energy.